2015
DOI: 10.3892/ol.2015.3176
|View full text |Cite
|
Sign up to set email alerts
|

Salivary duct carcinoma: A clinopathological report of 11 cases

Abstract: Abstract. The aim of the present study was to summarize the clinicopathological and immunohistochemical characteristics of salivary duct carcinoma (SDC) and to evaluate the currently available treatment modalities. Between 2001 and 2011, 11 patients with SDC were diagnosed and treated at the Affiliated Hospital of Stomatology of Nanjing University (Nanjing, Jiangsu, China). The present study retrospectively reviewed the clinicopathological and immunohistochemical data of these 11 patients and the results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 21 publications
3
24
1
1
Order By: Relevance
“…SDC is most frequently seen in men aged 50 or older [4, 6, 16, 18, 19] and is one of the more rare malignant salivary tumors. In one series of all salivary gland cancers during a 5-year period in Finland, it was estimated that 4–6% were SDC [20].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…SDC is most frequently seen in men aged 50 or older [4, 6, 16, 18, 19] and is one of the more rare malignant salivary tumors. In one series of all salivary gland cancers during a 5-year period in Finland, it was estimated that 4–6% were SDC [20].…”
Section: Introductionmentioning
confidence: 99%
“…T3 or T4), with figures ranging from 35–74% [2, 47, 9, 11, 12, 14, 15, 18, 22, 3138]. Two separate National Cancer Data Base (NCDB) studies, each with over 400 patients, found that 40–42% of patients presented with advanced T stage [36, 38].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations